2021
DOI: 10.1002/jeq2.20283
|View full text |Cite
|
Sign up to set email alerts
|

Split‐nitrogen application with cover cropping reduces subsurface nitrate losses while maintaining corn yields

Abstract: Artificial subsurface drainage is essential to sustain crop production in many areas but may also impair water quality by exacerbating nitrate (NO 3 )-nitrogen (N) delivery downstream. Cover crops and split-N application have been promoted as key conservation practices for reducing NO 3 -N losses, but few studies have simultaneously assessed their effect on water quality and crop productivity. A field study was conducted to evaluate the effects of N application timing and cover crops on subsurface drainage NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…(2017) and Preza‐Fontes et al. (2021) found the same corn yields in all years for similar fertilizer treatments as in our study. Results in Jaynes (2015) differed where they reported an increase in corn yield with a sidedress application compared with fall and preplant.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…(2017) and Preza‐Fontes et al. (2021) found the same corn yields in all years for similar fertilizer treatments as in our study. Results in Jaynes (2015) differed where they reported an increase in corn yield with a sidedress application compared with fall and preplant.…”
Section: Resultssupporting
confidence: 87%
“…The SS mid-vegetative season surface applied urea would require precipitation to be moved into the corn root zone and to reduce the risk of ammonia losses (the SS inseason urea application included a urease inhibitor) (Fenn & Miyamoto, 1981). Pittelkow et al (2017) and Preza-Fontes et al (2021) found the same corn yields in all years for similar fertilizer treatments as in our study. Results in Jaynes ( 2015) differed where they reported an increase in corn yield with a sidedress application compared with fall and preplant.…”
Section: Corn Plant Sensing and Crop Productionsupporting
confidence: 84%
See 1 more Smart Citation
“…Preza‐Fontes et al. (2021) previously described field and plot management. Briefly, each 0.85‐ha plot was tile‐drained at ∼1.2 m depth with 18 m spacing (drainage design coefficient, or the rate at which water is to be removed from a drainage area, usually within 24 h: 9.5 mm d −1 ), and each plot was separated by border tiles (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Both natural and anthropogenic factors influence NO 3 leaching, including soil properties, climate and farming practices. Reports on N leaching are extensive (Padilla et al 2018), with previous work highlighting crop choice, N fertilizer management (rate, source, timing and placement), tillage, cover crops and soil texture and carbon as influential factors, among others (Zhou and Butterbach-Bahl 2014, Eagle et al 2017, Thapa et al 2018, Hess et al 2020, Ying et al 2020, Preza-Fontes et al 2021. Regardless of experimental conditions, N fertilizer rate is a particularly strong predictor of N losses (Lawlor et al 2008, Xia et al 2017, Wang et al 2019, Huddell et al 2020.…”
Section: Introductionmentioning
confidence: 99%